Sounder - Armstrong, William Howard, 1914-; Barkley, James (New York, Harper & Row, 1969)
Angry and humiliated when his sharecropper father is jailed for stealing food for his family, a young black boy grows in courage and understanding by learning to read and with the help of the devoted dog Sounder.
Children's Catalog (Wilson)
Junior High School Library Catalog (Wilson)
Elementary School Library Collection (Bro-Dart)
5.2
5-8
Newbery 1970 Medal
Keywords: Afro-Americans -- Fiction; Dogs -- Fiction; Family life -- Fiction; Poverty -- Fiction; Blacks -- Fiction; Poverty -- Fiction